Hotspots of kidney failure: Analysing Australian metropolitan dialysis demand for service planning - Dominic Keuskamp; Christopher E. Davies; Shilpanjali Jesudason; Stephen P. McDonald (Elsevier, 2024)
Objective: To locate incident hotspots of dialysis demand in Australian capital cities and measure association with prevalent dialysis demand and socioeconomic disadvantage. Methods: A retrospective cohort study used Australia and New Zealand Dialysis and Transplant Registry data on people commencing dialysis for kidney failure (KF) resident in an Australian capital city, 1 January 2001 - 31 December 2021. Age-sex-standardised dialysis incidence was estimated by Statistical Area Level 3 (SA3) and dialysis prevalence by SA2. Results: A total of 32,391 people commencing dialysis were referenced to SA3s within city metropolitan areas based on residential postcode. Incident hotspots were located in Western Sydney. The highest average annual change of standardised incidence was 8.3 per million people (false discovery rate-corrected 95% CI 1.0,15.7) in Mount Druitt, reflecting a 263% increase in absolute demand from 2001-3 to 2019-21. Incident dialysis for diabetic kidney disease contributed substantially to total growth. Incident hotspots were co-located with areas where prevalent dialysis demand was associated with socioeconomic deprivation. Conclusions: Novel spatial analyses of geo-referenced registry data located hotspots of kidney failure and associated socio-demographic and comorbid states. Implications for Public Health: These analyses advance current abilities to plan dialysis capacity at a local level. Hotspots can be targeted for prevention and slowing the progression of kidney disease.